2004
DOI: 10.1023/b:ququ.0000013236.29205.a6
|View full text |Cite
|
Sign up to set email alerts
|

Response Effects in Surveys on Children and Adolescents: The Effect of Number of Response Options, Negative Wording, and Neutral Mid-Point

Abstract: Abstract. Social researchers increasingly survey children and young adolescents. They are convinced that information about perspectives, attitudes, and behaviors of children should be collected from the children themselves. Methodological expertise on surveying children is still scarce, and researchers rely on ad-hoc knowledge from fields such as child psychiatry and educational testing, or on methodological knowledge on surveying adults. Regarding adults, empirical evidence shows that respondent characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
173
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(184 citation statements)
references
References 31 publications
3
173
0
8
Order By: Relevance
“…A weakness with surveys (both children and adults) is the tendency of respondents to give more or less superficial responses that appear reasonable or acceptable, without going through all the cognitive steps involved in an optimal question-answering process. Low motivation, low cognitive ability, and difficult or poorly worded questions or statements are the main causes for respondents providing a merely satisfactory response instead of a carefully considered optimal one [58]. To minimize the possibility of too difficult or poorly worded statements, the survey statements were given to the educators in charge of the classes ahead of time to assess their appropriateness.…”
Section: Discussionmentioning
confidence: 99%
“…A weakness with surveys (both children and adults) is the tendency of respondents to give more or less superficial responses that appear reasonable or acceptable, without going through all the cognitive steps involved in an optimal question-answering process. Low motivation, low cognitive ability, and difficult or poorly worded questions or statements are the main causes for respondents providing a merely satisfactory response instead of a carefully considered optimal one [58]. To minimize the possibility of too difficult or poorly worded statements, the survey statements were given to the educators in charge of the classes ahead of time to assess their appropriateness.…”
Section: Discussionmentioning
confidence: 99%
“…The relative ranking of immediacy between conditions is also the same, with the high immediacy robot being perceived as most immediate, then the human, followed by the low immediacy robot condition. However, there are also some differences as the child scores are more tightly bunched together; this could reflect their different (yet consistent) interpretation of negatively formulated questions [22], or more limited language understanding impeding the data quality [21]. A two-way ANOVA was conducted to examine the effect of age group (child/adult) and condition (high/low robot, human) on the immediacy rating.…”
Section: Nonverbal Immediacy Resultsmentioning
confidence: 99%
“…Cronbach's alpha measures the internal consistency of questionnaire items. Whilst some inconsistency is likely due in part to child interpretations of negatively worded items [22], there are some items within the questionnaire that the robot behaviour itself is probably not consistent in. For example, the questions related to smiling and frowning are opposites of each other in terms of calculating a value for the scale, but could both be answered as 'never' performed, as the robot does not have moveable facial features.…”
Section: Using Nonverbal Immediacy In Hrimentioning
confidence: 99%
“…Methodological research among children has shown that an even number of answering options is optimal because children have a strong tendency to choose the midpoint of the scale when using uneven answering options (Borgers, Hox, and Sikkel, 2004). In addition, four answering options make it easier for children to choose but still provide enough variance (Borgers et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, four answering options make it easier for children to choose but still provide enough variance (Borgers et al, 2004).…”
Section: Methodsmentioning
confidence: 99%